EKSITENSI LEMBAGA HIPOTIK DAN CREDITVERBAND SETELAH BERLAKUNYA UNDANG - UNDANG NOMOR 4 TAHUN 1996 - Happy, Niedia; Mudana, I Nyoman (Kertha Semaya : Journal Ilmu Hukum, 2015)
Before enactment of legislation - Act No. 4 of 1996 on the rights of dependents (UUHT)so all the imposition of any debt security over immovable charged to institutions guaranteeand creditverband. Along with the times then feels that the provisions on institutions guarantee andcreditverband considered is no longer compatible with the principle - the principle of national law. So it must to know how existence of the institution guarantee andCreditverband after enactment UUHT In This writing method Normative legal research which is based on the theories of legal materials and in accordance with legislation. After the entry into force UUHT then since the debt any encumbrances on immovable switch to guarantee rights but the presence of agency mortgages are still recognized but is only charged on the loading of ships, aircraft, helicopters and trains that already has a registration mark which may be charged to agency mortgages. Institute creditverband after enactment UUHT then it is no longer valid.
Keywords: Existence, Guarantee Institutions and Creditverband